2019
DOI: 10.2147/copd.s187596
|View full text |Cite
|
Sign up to set email alerts
|

<p>Normal lung attenuation distribution and lung volume on computed tomography in a Chinese population</p>

Abstract: Backgroud and objectives: Although lung attenuation distribution and lung volume on computed tomography (CT) have been widely used in evaluating COPD and interstitial lung disease, there are only a few studies regarding the normal range of these indices, especially in Chinese subjects. We aimed to describe the normal range of lung attenuation distribution and lung volume based on CT. Methods: Subjects with normal lung function and basically normal chest CT findings (derivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
(84 reference statements)
8
16
1
Order By: Relevance
“…Cheng et al . analysed 2351 lung-healthy patients for lung density on CT and found a low-density percentage of 17–19% [ 23 ], comparable to the values reported in Table 1 . It is therefore possible that in a patient population with lung disease and a significantly higher proportion of emphysema, CT-based quantification and analysis of low-density lung-volume could still be useful to model the severity of COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…Cheng et al . analysed 2351 lung-healthy patients for lung density on CT and found a low-density percentage of 17–19% [ 23 ], comparable to the values reported in Table 1 . It is therefore possible that in a patient population with lung disease and a significantly higher proportion of emphysema, CT-based quantification and analysis of low-density lung-volume could still be useful to model the severity of COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, we also found that the left, right, and bilateral lung mean expiratory lung density showed signi cantly positive correlation with FEV1/FVC. This is in accordance with the conclusion arrived at by previously published studies [30][31][32].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, there were similar correlation findings of PFT parameters with lung CT density-volumetry, compatible with the literature 5,7,11,19 . TLV and TLD in the current study were found to be 3820±1272.35 and -1597.17±295.70, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In this paper, we aimed to evaluate PFT and CT volumetric results in normal population and whether CT volumetric values could be a good predictor for the assessment of PFT specially in extraordinary situations such as coronavirus disease-2019 (COVID- 19), in which PFT is impossible to be performed.…”
Section: Introductionmentioning
confidence: 99%